Hemorrhagic pulmonary leptospirosis: three cases from the Yucatan peninsula, Mexico Leptospirose hemorrágica pulmonar: três casos na península de Yucatán, México - Jorge Zavala-Velázquez; María Cárdenas-Marrufo; Ignacio Vado-Solís; Marco Cetina-Cámara; José Cano-Tur; Hugo Laviada-Molina (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
Three leptospirosis cases with lung involvement are reported from the Yucatan Peninsula, Mexico. All three patients were admitted to the intensive care unit due to acute respiratory failure. Treatment with antibiotics resulted in favorable evolution despite the negative prognosis. Leptospirosis should be included in the differential diagnosis of patients with fever and lung involvement. Analisamos três casos de leptospirose com envolvimento pulmonar na Península Yucatán, México. Os três pacientes com seqüelas pulmonares entraram na unidade de cuidados intensivos devido à insuficiência respiratória grave. Todos os casos evoluíram favoravelmente ao tratamento com antibióticos, apesar do prognóstico negativo. Leptospirose deve ser incluída no diagnóstico diferencial de pacientes com febre e comprometimento pulmonar.